Quantificação de hidrocarbonetos policíclicos aromáticos no material particulado e sua influência na saúde em Goiás - Castel, Dênia Kássia Aureliano Dal (2018)
There are more than 100 different polycyclic aromatic hydrocarbons (PAH) in the atmosphere, of which 16 are considered priority pollutants by the United States Environmental Protection Agency (USEPA) because they have mutagenic and/or carcinogenic characteristics. The objective of this unprecedented study was to quantify these PAH in the particulate matter (PM) of Goias, and to identify its sources and health implications. The concentrations of PM in Goiania varied from 41 to 116 μg.m- ³, and in Anapolis the concentrations were higher, 97 to 165 μg.m- ³. Several times the concentrations of PM collected (monthly) in the city of Anapolis exceeded the limits recommended by CONAMA Resolution 03/90 (150 µg.m-3 ) and Goias State Decree number 8544/78 (120 µg. m -3 ), and the average concentration at this site (135 ± 10 μg.m- ³) was higher than the maximum concentration established by state legislation (120 µg.m-3 ). The sum of the concentrations of the 24 HPA analyzed in the PM samples from Goiania ranged from 5.2 to 10.0 ng.m-3 (7.0 ± 1.8 ng.m-3 ). In the city of Anapolis the sum of the concentrations of the 24 PAH was larger and more variable, 6.9 to 19.2 ng.m-3 (12.4 ± 3.8 ng.m-3 ) which may be due to the proximity between the sampler and two highways. In both sample sites statistically significant seasonal variations were not observed in PM and PAH concentrations. The most abundant HPA in these sites was Carbazole, which is originated in the burning of fossil fuel. The diagnostic ratios, ratios among PAH concentrations, confirmed that the main source of particulate matter in the region was the vehicular emission, mainly diesel vehicles. The mean values of benzo[a]pyrene equivalent index (BaPE) were 0.24 ± 0.19 ng.m-3 (n = 10) in the PM samples collected in Goiania, and 0.64 ± 0.38 ng .m-3 (n = 13) in Anapolis. For two samples collected in Anapolis the BaPE values exceeded the limit recommended by the World Health Organization (WHO - 1 ng.m-3 ). Another worrisome was the significant linear correlation between PM and PAH concentrations with some hospitalization data and deaths due to respiratory, circulatory and neoplastic diseases. Therefore, this work showed, for the first time, the concentrations of PAH in PM collected in Goias, and that these particulates can cause damage to health. New calculations will be performed to evaluate these correlations, increasing the number of samples and using programs developed for these analyzes.